Designing an effective EDRMS based on Alter's Service Work System model - Goldschmidt, P.; Joseph, Pauline; Debowski, S. (Emerald Group Publishing Limited, 2012)
Purpose: The purpose of the paper is to develop a framework for electronic document and records management systems (EDRMS) as a Service Work System. This enhanced overview of EDRMS support strategies suggests that the increasing shift in recordkeeping responsibilities to users requires greater consideration of the core activities that should be supported by RM professionals. The paper seeks to examine the concept of records management (RM) service delivery using this model.Design/methodology/approach: The authors offer a complementary approach for EDRMS analysis, design and implementation augmenting the human computer interaction (HCI) approach. They show how ideas related to services can be incorporated into the existing RM domain and can enrich current approaches within this field. Findings: The changing context from records management suggests a need to shift the RM orientation from a systems domain approach to a Service Work System model. A reorientation of records management emphasises stronger consideration of user needs and stakeholder expectations. The education of records management professionals to accommodate RM users' requirements will also encourage a stronger concern for the development of EDRMS that are “fit for purpose”.Practical implications: Records management theory and practice would benefit from a shift in orientation from a systems driven Work Systems Model to a Service Work Systems Model. The shift to a Service Work Systems Model will necessitate a stronger consideration of user needs and stakeholder expectations and increased focus and approach to learning and education of records management professionals and users. Social implications: The concept of Service Work Systems to the development of electronic document and records management systems is introduced. Originality/value: The paper introduces the concept of Service Work Systems to the development of electronic document and records management systems for RIM professionals.